Salmonella Reprograms Nucleotide Metabolism in Its Adaptation to Nitrosative Stress - Liam F. Fitzsimmons; Lin Liu; Ju-Sim Kim; Jessica Jones-Carson; Andrés Vázquez-Torres (mBio, 2018)
ABSTRACT The adaptations that protect pathogenic microorganisms against the cytotoxicity of nitric oxide (NO) engendered in the immune response are incompletely understood. We show here that salmonellae experiencing nitrosative stress suffer dramatic losses of the nucleoside triphosphates ATP, GTP, CTP, and UTP while simultaneously generating a massive burst of the alarmone nucleotide guanosine tetraphosphate. RelA proteins associated with ribosomes overwhelmingly synthesize guanosine tetraphosphate in response to NO as a feedback mechanism to transient branched-chain amino acid auxotrophies. Guanosine tetraphosphate activates the transcription of valine biosynthetic genes, thereby reestablishing branched-chain amino acid biosynthesis that enables the translation of the NO-consuming flavohemoglobin Hmp. Guanosine tetraphosphate synthesized by RelA protects salmonellae from the metabolic stress inflicted by reactive nitrogen species generated in the mammalian host response. This research illustrates the importance of nucleotide metabolism in the adaptation of salmonellae to the nutritional stress imposed by NO released in the innate host response. IMPORTANCE Nitric oxide triggers dramatic drops in nucleoside triphosphates, the building blocks that power DNA replication; RNA transcription; translation; cell division; and the biosynthesis of fatty acids, lipopolysaccharide, and peptidoglycan. Concomitantly, this diatomic gas stimulates a burst of guanosine tetraphosphate. Global changes in nucleotide metabolism may contribute to the potent bacteriostatic activity of nitric oxide. In addition to inhibiting numerous growth-dependent processes, guanosine tetraphosphate positively regulates the transcription of branched-chain amino acid biosynthesis genes, thereby facilitating the translation of antinitrosative defenses that mediate recovery from nitrosative stress.